2013
DOI: 10.1097/01.asw.0000426718.59326.bb
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of Nursing Home Factors Associated with Successful Implementation of Clinical Decision Support Tools for Pressure Ulcer Prevention

Abstract: The learning from On-Time QI offers several lessons associated with facility factors that contribute to high level of implementation of a QI-HIT program in a nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 9 publications
1
73
0
Order By: Relevance
“…For DSCUs with this orientation, the attitude of the key persons in implementing the care program is crucial. Earlier research on implementation of a multifaceted intervention in nursing homes also showed that having a team champion (for example, someone who is passionate about the use of the care program) has a substantial impact on the effectiveness of a team to adapt to innovation [9]. Implementation indeed seemed to be facilitated when an enthusiastic key person was willing to commit to the care program and that absence or departure of such a team champion seriously impacted the implementation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For DSCUs with this orientation, the attitude of the key persons in implementing the care program is crucial. Earlier research on implementation of a multifaceted intervention in nursing homes also showed that having a team champion (for example, someone who is passionate about the use of the care program) has a substantial impact on the effectiveness of a team to adapt to innovation [9]. Implementation indeed seemed to be facilitated when an enthusiastic key person was willing to commit to the care program and that absence or departure of such a team champion seriously impacted the implementation process.…”
Section: Discussionmentioning
confidence: 99%
“…Next to the Grip on Challenging behavior project, projects to improve care for residents with depression, to improve medication administration, to prevent pressure ulcers and to better detect and treat pain are just a few other examples of recent attempts to establish evidence-based care of high quality [69]. Implementing such new interventions in nursing homes is difficult, for the structure and culture of the nursing home setting is complex and heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…12 These factors align with factors important to other types of improvement initiatives implemented in nursing homes. The training of supervisors and administrators in addition to direct care staff was critical in a successful mouth care program, 13 for example, and management support and integration of learning into job descriptions were key factors in a mental health learning initiative.…”
Section: Introductionmentioning
confidence: 84%
“…These job categories were chosen because of their relevance to PrU prevention efforts. 6,12 Multiple job categories were selected to aid in data triangulation. A telephone interview was scheduled with those who responded.…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation